Carbohydrate-deficient glycoprotein syndromes. Issue 893 (1st March 2000) - Gordon, Neil
Abstract : Four types of carbohydrate-deficient glycoprotein syndrome have been described, and the cause of two of them has been found. The symptoms and signs of these syndromes are described, with variations that occur at different ages. The commonest is type Ia with an autosomal recessive form of inheritance, and the gene responsible has been mapped to 16p. The typical pathology is atrophy of the cerebellum and brainstem, sometimes also involving the cortex, although both the pathology and the biochemical deficiencies vary between different types of syndrome. The diagnosis depends firstly on recognising the clinical features, including the presence of complications such as thyroid disorders. Then biochemical tests can be carried out, especially chromatographic carbohydrate-deficient transferrin assay and isoelectric focusing of serum transferrin. The prognosis depends on the complications, renal, hepatic, and cardiac, but affected children will be severely handicapped. Therefore treatment consists mainly of coping with the complications, and supporting the child and the family. Oral infusion of mannose can be effective in type Ib disease.